2021
DOI: 10.1097/ncc.0000000000000750
|View full text |Cite
|
Sign up to set email alerts
|

Reflections of Healthcare Experiences of African Americans With Sickle Cell Disease or Cancer: A Qualitative Study

Abstract: Background The experiences of African American adult patients before, during, and after acute care utilization are not well characterized for individuals with sickle cell disease (SCD) or cancer. Objective To describe the experiences of African Americans with SCD or cancer before, during, and after hospitalization for pain control. Methods We conducted a qualitative study among African American participants … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 47 publications
1
13
0
Order By: Relevance
“…In particular, they expressed concerns that they were not being heard and were often mistreated. These concerns are consistent with the health care experiences expressed among patients with SCD in other studies [ 41 , 42 ]. This reflects that although implementing mHealth in self-management interventions could potentially be effective in increasing communication with the health care providers, there is still a need to improve the SCD patient-provider interactions, particularly in acute settings.…”
Section: Discussionsupporting
confidence: 90%
“…In particular, they expressed concerns that they were not being heard and were often mistreated. These concerns are consistent with the health care experiences expressed among patients with SCD in other studies [ 41 , 42 ]. This reflects that although implementing mHealth in self-management interventions could potentially be effective in increasing communication with the health care providers, there is still a need to improve the SCD patient-provider interactions, particularly in acute settings.…”
Section: Discussionsupporting
confidence: 90%
“…42,43 Adult health care (particularly ED) provider biases and negative attitudes have been recognized as major barriers to optimal pain management in SCD. 8,11,44,45 Interestingly, ED providers in our needs assessment indicated that they felt they had the training and resources to manage patients with SCD. However, only a few actually reported knowing about the NHLBI recommendations for the treatment of vasoocclusive pain.…”
Section: Discussionmentioning
confidence: 97%
“…These clinician-based biases negatively impact the quality of pain management, treatment outcomes, healthcare experiences, and patient biopsychosocial-spiritual health, especially among minority populations (Maina et al, 2018; Thames et al, 2019). For instance, Black patients with sickle cell disease (SCD) or cancer reported perceived bias from healthcare providers as reflected by delayed treatment and lack of communication (Dyal et al, 2019). Individuals with SCD were also confronted with accusations of drug-seeking behavior, perceived mistreatment, and feelings of not being heard or believed.…”
Section: Introductionmentioning
confidence: 99%